Meningkatkan Prestasi Belajar Pendidikan Agama Kristen Melalui Penggunaan Media Pembelajaran “Quizizz” di Masa Pandemi Covid-19 - Priskila Issak Benyamin; Yuel Sumarno; Ucok Sinaga (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2021)
Online learning in the pandemic era tends to make students passive in class. Therefore, researchers use Quizizz Learning media to increase student activity and achievement in PAK learning at SMA Negeri 16 Jakarta in the covid-19 era. The purpose of this study was to determine the increased inactiveness and learning achievement of Christian Religious Education for class XII students of SMA Negeri 16 West Jakarta through the learning media "Quizizz." This research uses the classroom action research method. The researcher was directly involved in the class action process in this study. The researcher acts as a teacher to teach and assess students' activeness and learning achievement. The sample-set was nineteen students from class XII SMA Negeri 16 West Jakarta. This study indicates that the Quizizz learning media increases student activity in class and student achievement.